Computing the Reverse Eccentric Connectivity Index for Certain Family of Nanocone and Fullerene Structures. (30th March 2016) - Gao, Wei; Farahani, Mohammad Reza
Abstract : A large number of previous works reveal that there exist strong connections between the chemical characteristics of chemical compounds and drugs (e.g., melting point and boiling point) and their topological structures. Chemical indices introduced on these molecular topological structures can help chemists and material and medical scientists to grasp its chemical reactivity, biological activity, and physical features better. Hence, the study of the topological indices on the material structure can make up the defect of experiments and provide the theoretical evidence in material engineering. In this paper, we determine the reverse eccentric connectivity index of one family of pentagonal carbon nanocones P C N 5 [ n ] and three infinite families of fullerenes C 12 n + 2,   C 12 n + 4, and C 18 n + 10 based on graph analysis and computation derivation, and these results can offer the theoretical basis for material properties.